Comportamento, competência social e qualidade de vida na Doença de Huntington - Silva, Caroline Stephanie Da (2015)
ABSTRACT:Purpose: investigating the behavior, the social competence and the quality of life of individuals who carry Huntington Disease.Methods: the sample was constituted for 30 participants, from 33 to 79 years old, divided in two groups: 15 participants in the experimental group, who were previously diagnosed with Huntington Disease and 15 participants in the comparative group, equally paired according to age and education. To assess this individuals were applied, on their caregivers, the Behavioral Inventory, constituted by the Adult Behavior Checklist and the Quality of Life Questionnaire WHOQOL - 100 were used to asses these individuals.Results: the individuals in the experimental group have presented statistically significant differences when compared to the control group, according to their caregivers' opinion, with high scores for internalizing factors (anxiety, depression, isolation, somatic complaints), total problems and other problems like: thinking, attention and hyperactivity problems, from the behavioral inventory. In the Quality of Life Questionnaire the experimental group has also presented statistically significant differences when compared to the control group, in all domains (physical, psychological, level of independence, social relationships, environment and religious aspects) and in most of the assessed aspects they presenting a low average of quality of life, while the control group has presented a high average.Conclusion: individuals with HD present behavioral, social competence and quality of life profile differentiated and with alterations, according to their caregivers, when it was related to the comparative group. Huntington's disease is limiting, progressive and also appears to be responsible for the set of behavioral change, social competence and quality of life reported by their caregivers.